Analisis Strategi Bauran Pemasaran dalam Meningkatkan Daya Saing dan Pertumbuhan Penjualan pada Perusahaan Konveksi I’nine - Yusril Mahendra; Angga Nadiyanto Prastian (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the implementation of the 7P marketing mix—Product, Price, Place, Promotion, People, Process, and Physical Evidence—at I'NINE, a business engaged in the production of women's workout apparel. The research adopts a qualitative descriptive approach, utilizing data collection techniques such as interviews with the business owner, observation of production and marketing activities, and documentation of various physical aspects of the business. The research findings indicate that, in general, I'NINE has applied the marketing mix elements quite well. The products offered are of good quality and meet market needs, although there is still a lack of design variety. Pricing is set competitively based on market conditions and product quality; however, some customers perceive the prices as relatively high. The production site is strategically located and easily accessible, although it has limited storage space for raw materials and finished goods. In terms of promotion, I'NINE mainly relies on word-of-mouth and has yet to fully utilize digital media such as social media platforms and online marketplaces. The business operates with a limited but solid human resource team that demonstrates strong commitment and teamwork. The production process follows a structured sequence based on established internal standards. Physical evidence, including brand labels, product packaging, and the appearance of the workshop, is present but has not yet been optimized to project a highly professional image to customers. In conclusion, I'NINE has significant growth potential if it can enhance certain marketing aspects such as digital promotion, product diversification in line with market trends, and improved human resource management. This research is expected to serve as a reference for other small-scale garment businesses in developing more effective and sustainable marketing strategies.